Effects of acute pre-treatment with ethanolamine on isoprenalineinduced myocardial infarction in adult Wistar rats - Garson, C.N.; Blackhurst, D.M.; Gwanyanya, A.; Kelly-Laubscher, R.F. (SA Heart Journal, 2017)
Ethanolamine (Etn), a biogenic amine, protects isolated hearts against MI, but its effects in vivo are unknown. In this study, we investigated the effects of Etn pretreatment on isoprenaline (ISO)-induced MI in vivo. Wistar rats were treated with either Etn (10mg.kg-1, i.p.) or saline, prior to either ISO (67mg.kg-1, s.c.) or saline. Haemodynamic- and electrocardiographic parameters were recorded under anaesthesia, 24 hours post-treatment with ISO. Infarct sizes were determined by triphenyltetrazolium chloride staining. Oxidative stress plasma parameters, conjugated dienes (CD) and thio-barbituric acid reactive substances (TBARS), were measured by spectrophotometric analysis. Etn decreased ISO-induced pathological Q-waves, but had no effect on ISO-induced low-voltage electrocardiogram. In addition, Etn decreased overall mortality induced by ISO treatment. However, Etn did not prevent ISO-induced infarction or the systolic- and diastolic hypotensive effects. Etn also enhanced the ISO-induced increase in heart-to-body weight ratio, and reversed the decrease in lungs-to-body weight ratio. Neither ISO nor Etn altered CD or TBARS. These results suggest that, despite a tendency to modulate cardiac electrical activity, Etn did not prevent ISO-induced MI or myocardial dysfunction in vivo.